Birodalmi helytartók I-II. . Governors of Empire - part 1, 2 - Tóth, Tamás (MTV Dokumentumfilm Studio, 1996)
Film about the communist dictatorship in Hungary, with the focus on Mátyás Rákosi, the Imre Nagy group and the 1956 Hungarian Revolution. Copious use of excerpts from Soviet and Hungarian archival newsreels.